2010
DOI: 10.1186/1742-4690-7-114
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of HIV-1-host interaction: role of the Vpu accessory protein

Abstract: Viral protein U (Vpu) is a type 1 membrane-associated accessory protein that is unique to human immunodeficiency virus type 1 (HIV-1) and a subset of related simian immunodeficiency virus (SIV). The Vpu protein encoded by HIV-1 is associated with two primary functions during the viral life cycle. First, it contributes to HIV-1-induced CD4 receptor downregulation by mediating the proteasomal degradation of newly synthesized CD4 molecules in the endoplasmic reticulum (ER). Second, it enhances the release of prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
99
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(102 citation statements)
references
References 163 publications
(333 reference statements)
3
99
0
Order By: Relevance
“…9 Myeloid-lineage cells resist HIV-1 replication due to the constitutive high expression of restriction factors, including APOBEC3G, SAMHD1, tetherin, and Mx2. These factors can act on different stages of HIV-1 replication such as viral RNA synthesis (APOBEC3G), [12][13][14][15][16][17][18] reverse transcription (SAMHD1), [19][20][21][22] viral release (tetherin), [23][24][25][26] and integration (Mx2). 27 However, HIV-1 and HIV-2 encode different proteins (Vif, Vpx, and Vpu) to counteract these restriction factors, but whether they are regulated in CD34 1 cells has not been studied before.…”
Section: Recent Studies Showed That Infection Of Cd34mentioning
confidence: 99%
“…9 Myeloid-lineage cells resist HIV-1 replication due to the constitutive high expression of restriction factors, including APOBEC3G, SAMHD1, tetherin, and Mx2. These factors can act on different stages of HIV-1 replication such as viral RNA synthesis (APOBEC3G), [12][13][14][15][16][17][18] reverse transcription (SAMHD1), [19][20][21][22] viral release (tetherin), [23][24][25][26] and integration (Mx2). 27 However, HIV-1 and HIV-2 encode different proteins (Vif, Vpx, and Vpu) to counteract these restriction factors, but whether they are regulated in CD34 1 cells has not been studied before.…”
Section: Recent Studies Showed That Infection Of Cd34mentioning
confidence: 99%
“…It has been shown that the Vpu-mediated degradation of CD4 happens via two independent mechanisms: the viral protein can either trigger proteasomal degradation of the receptor by linking it to β-TrCP, a component of the SCF β-TrCP E3 Ub ligase complex [12]. Vpu can also act in a variant Endoplasmic Reticulum-Associated Degradation (ERAD) pathway to independently mediate the retention of CD4 in the ER, a function traditionally attributed to Env [13][14][15]. However, the exact pathways used by the HIV-1 proteins to divert the internalized CD4 molecules to lysosomal degradation and hamper their recycling remain to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Vpu is a 16-kDa transmembrane protein encoded by HIV-1 and some simian immunodeficiency virus (SIV) 2 strains that interferes with multiple host-cell functions to enhance viral propagation and pathogenesis (1). One of the best characterized effects of Vpu is the down-regulation of CD4, a component of the host immune system that doubles as the primary HIV-1 receptor.…”
mentioning
confidence: 99%